The Relationship developed between Law and Regulation and its Effect on the Rules of Distribution of Jurisdiction Between the Legislature and Executive Authority: A comparative study - الشاوي, سرى حارث (Journal of Legal Sciences, 2021)
Sort out the stability of the principle of separation of power to stabilize the rules for the distribution of power to the three state authorities (legislative, executive and Judicial), this, in turn led to emergence of the principle of legislative unilateralism, which means that the legislative authority is unique and not the other by exercising legislative competence, except with the permission of the legislative or the provisions of the constitution, this led to the emergence of what is known as the traditional relationship between law and regulation. However, this principle began to lose it, severity due the political, social and economic condition which changed the relationship between the law and the regulation, consequently, the legislative scope of both the parliament and the government has changed.This study focuses on the evolution of the relationship between law and regulation, and it impact on changing the legislative field for both the legislative and executive.